2021
DOI: 10.2147/ccide.s310026
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Maternal Dental Anxiety and Children’s Dental Caries in the Eastern Province of Saudi Arabia

Abstract: Purpose: Dental anxiety is a barrier to dental care utilization and is associated with poor oral health outcomes. The aim of the study was to assess the relationship between dental anxiety of mothers and dental caries of their children in the Eastern Province, Saudi Arabia. Methodology: A cross-sectional study was conducted on a sample of mother-child pairs (N= 199) in Dammam, AlKhobar, and Dhahran, Saudi Arabia. Dental caries experience among children was determined using dmft/DMFT indexes following the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In India, most children have their FDV after 5 years of age, with dental caries being the most prevalent cause 9 . Dental anxiety is also common among parents and is considered a cause for avoiding or delaying dental check‐ups for children 14 . Furthermore, low‐income families are more likely to have lower health literacy and use oral healthcare services infrequently 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, most children have their FDV after 5 years of age, with dental caries being the most prevalent cause 9 . Dental anxiety is also common among parents and is considered a cause for avoiding or delaying dental check‐ups for children 14 . Furthermore, low‐income families are more likely to have lower health literacy and use oral healthcare services infrequently 15 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Dental anxiety is also common among parents and is considered a cause for avoiding or delaying dental check-ups for children. 14 Furthermore, low-income families are more likely to have lower health literacy and use oral healthcare services infrequently. 15 Evidence suggests that parental commitment has a prominent role in effectively preventing ECC.…”
mentioning
confidence: 99%
“…Dental anxiety is one of the most significant obstacles on dental visits and is affiliated with bad oral health that puts the patients at higher risk of having a dental disease. In adults, the prevalence of higher levels of anxiety ranges from 11.6% to 19.1% (11).…”
Section: Resultsmentioning
confidence: 99%
“…An interesting finding in the current study was that mothers who were not regular dental visitors and perceived dental visits as stressful had higher rates of FV acceptance, contradicting the findings by Alhareky et al, who found that mothers' dental anxiety was associated with an increase in caries prevalence [ 48 ]. Other factors, such as mothers' age, socioeconomic status, and educational level, may have acted as moderators, weakening the relationship between maternal dental anxiety and dental caries and encouraging anxious mothers to seek preventive care [ 49 ].…”
Section: Discussionmentioning
confidence: 99%